Literature Review on the Implementation of the Pre-Employment Card Program in Indonesia - Keysa Fadhia Azahra; Danish Ammara; Pretty Novita Sari; Amalia Kurniawati (Riviera Publishing, 2025)
Unemployment remains a major issue in national development, primarily due to the skills gap between job seekers and industry needs. To address this issue, the government has launched the Pre-Employment Card Program, which aims to improve work and entrepreneurship competencies through digital-based training. This study aims to evaluate the implementation of the Pre-Employment Card Program using a public policy evaluation approach, including indicators of effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. The method used is a literature study by reviewing various sources related to program implementation. The research findings indicate that the Pre-Employment Card Program has achieved positive results, particularly in terms of effectiveness and efficiency through expanding access to training and using digital systems. However, this program still faces challenges such as a mismatch between training skills and industry needs, unequal access due to differences in digital literacy and internet access, and uneven training quality. From an evaluative perspective, this program is considered quite helpful in improving participant competency, but it has not been able to fully address structural unemployment in Indonesia. Therefore, improving the quality of the training curriculum, equitable digital access, and increasing the relevance of training to job market needs are crucial steps to maximize the benefits of the Pre-Employment Card Program in the future.